Efektivitas Manajemen Persediaan Bahan Baku Dan Biaya Produksi Menurut Perspektif Ekonomi Islam - Chusnul Chotimah; Fathmah Hanum; Abdus Salam (Cashless : Journal of Sharia Finance and Banking, 2023)
This article discusses the guidelines for raw material inventory management using the EOQ (Economic Order Quantity) method with company policies to seek a better understanding of how to handle raw material inventory management. Researchers want to discuss the Effectiveness of Raw Material Inventory Management and Production Costs According to the Perspective of Islamic Economics. The focus of this research is how to compare raw material ordering management according to CV company calculations. Jati Makmur with the EOQ (Economic Order Quantity) method and whether the production performance at CV. Jati Makmur has met the requirements of an Islamic Economics perspective? This study uses a quantitative approach and the research design is a survey model. Ary (1995) emphasized that besides being able to use the survey model to describe conditions with established criteria, it can also be used to investigate differences in these symptoms and to test hypotheses. The results showed that the raw material inventory control management implemented by CV. Jati Makmur is more efficient using the (Economic Order Quantity) method in maintaining the smooth production of plywood. Production Process of Raw Materials, and Production Costs in accordance with the requirements of the Islamic economy.